Diagnostic value and safety of dynamic MRI of contralateral breast and axilla in subjects with tissue expander. Issue 9 (September 2018) - Fausto, Alfonso; Bernini, Marco; Giacomo, Letizia Di; Schivartche, Vivian; Marcasciano, Marco; Casella, Donato; Volterrani, Luca; Mazzei, Maria Antonietta
Abstract: Introduction: To verify the diagnostic value of contrast-enhanced breast and axillary MRI in patients with tissue expander labeled as "MR-unsafe" and to confirm its safety. Patients and methods: Breast MRI examinations performed in patients with tissue expander in the period from August 2010 to December 2017 were reviewed after IRB approval. In the case of breast lesion or lymph node, breast MRI exams after definitive prosthetic replacement were used for comparison. Breast MRI was performed using 1.5 T equipment with a dedicated coil. The protocol included axial STIR sequence and axial dynamic sequence with fat suppression (1 pre-contrast and 4 post-contrast phases). Two radiologists experienced in breast imaging reviewed images using six parameters for image quality evaluation. t -Test for dependent samples, Wilcoxon and Sign test were used. Results: Twenty-three patients (49 ± 9 years, range 34–68 years) with tissue expander who underwent contrast-enhanced MRI were reviewed. Thirteen breast lesions (12.92 ± 4.84 mm) and eleven lymph nodes (11.00 ± 4.29 mm) were found. In breast MRI examinations used for comparison no significant difference was observed in breast lesions (12.69 ± 4.71 mm, P  = 0.707) or lymph node dimensions (10.58 ± 3.00 mm, P  = 0.538). No significant difference was observed in lesion classification. A significantly lower visibility was observed for vascular maps ( P  < 0.001). None of the patients reported sensations of heating or skin burns. None of the patients revealed any clinical effects or signs of pathology after MRI examination. Conclusion: When necessary, after adequate information and preparation, contrast-enhanced breast MRI can be performed in patients with tissue expanders maintaining its diagnostic value and safety.